The Principles of Supply Chain Strategy and Reinventing Government Supply Chain Service in the Era of Regional Economy - Guntoro, HM (ExcelingTech, 2020)
Abstract- This globalization era indicate that the world community, in general, has entered the stage of the age of high mass-consumption or fifth level. So, in this condition there is a necessity for application and practice of supply chain strategies for regional companies, where there was a shift in the dominant sectors of the goods and services in line with the increase in people's income. Facing the condition of the society, it is necessary to state administration and the supply chain role in providing services is a tremendously effective, efficient and professional manner. Governments need to develop service standards for each institution in the area assigned to provide services to the community. Deregulation and Debureaucratization absolutely must continue to be done by the supply chain and local rules should be evaluated regularly to continue to satisfy the supply chain service community.